Analysis of Risk Factors for Hemorrhagic Transformation of Cerebral Infarction and Recurrence of Cerebral Infarction: A Retrospective Study on Cerebral Infarction Patients with or without Hemorrhagic Transformation - Bao P; Ling L; Xiang L; Liu X; Zhang J; Yue W (International Journal of General Medicine)
Pengnan Bao,1 Ling Ling,2 Lei Xiang,2 Xueqing Liu,1 Jinwei Zhang,1 Wei Yue1,2 1Clinical College of Neurology, Neurosurgery and Neurorehabilitation, Tianjin Medical University, Tianjin, 300000, People’s Republic of China; 2Department of Neurology, Tianjin Huanhu Hospital, Tianjin, 300000, People’s Republic of ChinaCorrespondence: Wei Yue, Department of Neurology, Tianjin Huanhu Hospital, Jizhao Road No. 6, Jinnan District, Tianjin, 300000, People’s Republic of China, Tel +86-13752686958, Email hhyuewei2008@163.comBackground: Acute ischemic stroke, especially hemorrhage cerebral infarction (HCI), resulted in the leading causes of mortality and long-term disability across populations. However, fewer researches have focused on the risk factors of first admission and recurrence of HCI.Methods: The study included 1857 patients who underwent cerebral infarction with or without hemorrhagic transformation. Clinical characteristics were collected, and univariate and multivariate analysis were performed to explore the risk factors. The subgroup analysis of cerebral infarction recurrence was performed. ROC analysis was utilized, and AUCs were showed the diagnostic values of the risk factors.Results: Compared to the patients with non-hemorrhage cerebral infarction, the patients with hemorrhage cerebral infarction were older and had higher Neutrophil infiltration, AST expression, globulin and BUN, while had lower ALT expression, triglyceride, PT, APTT, homocysteine, d-dimer, CRP and glycosylated hemoglobin. Utilizing univariate and multivariate analysis, age, thrombolytic, Hb, AST and glycosylated hemoglobin were the risk factors between the patients with hemorrhagic cerebral infarction and non-hemorrhagic cerebral infarction. ROC analysis was performed to demonstrate that glycosylated hemoglobin was a diagnostic biomarker for the patients with hemorrhagic cerebral infarction and non-hemorrhagic cerebral infarction (AUC = 0.808). Utilizing univariate and multivariate analysis, age, hypertension history, LDL and MRS Score on admission were the risk factors between non-hemorrhagic cerebral infarction patients with first admission or the cerebral infarction recurrence. ROC analysis was performed to demonstrate MRS Score on admission was a diagnostic biomarker for recurrence of cerebral infarction in patients with non-hemorrhagic cerebral infarction (AUC = 0.708). Utilizing univariate and multivariate analysis, only hypertension history was the risk factors between hemorrhagic cerebral infarction patients with first admission or the cerebral infarction recurrence.Conclusion: In conclusion, age, hypertension history, LDL and MRS Score on admission were the risk factors between cerebral infarction patients with first admission or the cerebral infarction recurrence.Keywords: acute ischemic stroke, hemorrhage cerebral infarction, LDL, MRS Score, ROC